أثر التغليف البيئي على الجودة المدركة - نادر, نهادد; بلال, مروان (Latakia University Journal - Economic and Legal Sciences Series, 2018)
The objective of the study was to examine the effect of the environmental role of packaging on the perceived quality of soft goods. This effect was measured by distributing a statistical questionnaire to a group of shoppers in three commercial centers (Golden Mall, Spencer Mall, Mall of Iskandron) and data analysis using SPSS. In addition to highlighting the importance of preserving the environment both economically and socially by returning to a collection of literature related to the subject of the study. The study found that there is an impact of the environmental packaging on the perceived quality, especially with regard to the viability of recycling and reuse. There has also been a good environmental awareness among consumers, which may encourage producers to offer eco-friendly products. هدف البحث إلى دراسة أثر دور التغليف في حماية البيئة على الجودة المدركة للمنتجات الاستهلاكية، وتم قياس هذا الأثر من خلال توزيع استمارة إحصائية على مجموعة من المتسوقين في ثلاث مراكز تجارية هي (جولدن مول، سبنسر مول، مول اسكندرون) وتحليل البيانات باستخدام برنامج SPSS. بالإضافة إلى تسليط الضوء على أهمية الحفاظ على البيئة سواءً من الناحية الاقتصادية والاجتماعية وذلك بالعودة إلى مجموعة من الادبيات المتعلقة بموضوع الدراسة. وقد توصلت الدراسة إلى وجود أثر للتغليف البيئي على الجودة المدركة، وخاصة فيما يتعلق بقابلية الغلاف لإعادة التدوير وإعادة الاستخدام. كما تبين وجود وعي بيئي جيد لدى المستهلكين مما قد يشجع المنتجين على تقديم منتجات ذات أغلفة صديقة للبيئة.